2020
DOI: 10.1002/ange.201915819
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrolled Synthesis of n‐Type Conjugated Polymers

Abstract: Current approaches to synthesize π‐conjugated polymers (CPs) are dominated by thermally driven, transition‐metal‐mediated reactions. Herein we show that electron‐deficient Grignard monomers readily polymerize under visible‐light irradiation at room temperature in the absence of a catalyst. The product distribution can be tuned by the wavelength of irradiation based on the absorption of the polymer. Conversion studies are consistent with an uncontrolled chain‐growth process; correspondingly, chain extension pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…[121][122][123][124] Returning to the discussion on comparing the synthesis routes of CPs, as polymerization of n-type CPs often involves catalysts, it has been excluded from oCVD practice. 121,[153][154][155] Recently, Woods et al 156 reported a catalyst-free protocol for the synthesis of n-type CPs, although their precursors (e.g. lithium salt) are beyond the current scope of polymer CVD in general due to its extremely low vapor pressure at room temperature.…”
Section: A Chemical Structurementioning
confidence: 99%
“…[121][122][123][124] Returning to the discussion on comparing the synthesis routes of CPs, as polymerization of n-type CPs often involves catalysts, it has been excluded from oCVD practice. 121,[153][154][155] Recently, Woods et al 156 reported a catalyst-free protocol for the synthesis of n-type CPs, although their precursors (e.g. lithium salt) are beyond the current scope of polymer CVD in general due to its extremely low vapor pressure at room temperature.…”
Section: A Chemical Structurementioning
confidence: 99%